Method for producing heat-resistant resin composition
Patent Information
- Application Number
- JP2023500786
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-17
- Filing Date
- 2022-02-10
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-02-10
AI Technical Summary
【0006】 本発明の耐熱性樹脂組成物の製造方法は、マレイミド系共重合体(A)とABS系樹脂(B)を押出機で溶融混練する際に、ラジカル捕捉剤の存在下で行うことで、ABS樹脂中のポリブタジエンの劣化を抑制し、耐衝撃性に優れた耐熱性樹脂組成物が得られる。
Smart Images

Figure 0007634640000002 
Figure 0007634640000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a heat-resistant resin composition having excellent impact resistance. [Background technology]
[0002] ABS resin is a thermoplastic resin mainly composed of acrylonitrile, butadiene, and styrene, and is widely used in automobiles, home appliances, office equipment, housing construction materials, daily necessities, etc., taking advantage of its excellent mechanical strength, appearance, chemical resistance, moldability, etc. On the other hand, in applications requiring heat resistance, such as automobile interior materials, heat resistance may be insufficient. There are the following techniques for improving heat resistance, and maleimide copolymers and α-methylstyrene copolymers are used (Patent Documents 1 to 3). The higher the heat resistance of the maleimide copolymer, the more the heat resistance of the ABS resin can be improved with a small amount of addition, but the melt viscosity of the maleimide copolymer increases, and it is necessary to knead it at a high processing temperature in order to knead it uniformly with the ABS resin. In addition, a method for producing a thermoplastic resin is known in which a direct granulation method is adopted, which does not require a drying process that causes oxidative deterioration of the resin, and a specific phenolic compound is made to exist during direct granulation (Patent Document 4). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 58-183729 [Patent Document 2] JP 2003-41080 A [Patent Document 3] WO2010 / 082617 publication [Patent Document 4] Japanese Patent Application Publication No. 5-78430 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a method for producing a heat-resistant resin composition having excellent impact resistance. [Means for solving the problem]
[0005] As a result of investigations by the present inventors, it was found that by melt-kneading a maleimide copolymer and an ABS resin in an extruder in the presence of a radical scavenger, degradation of polybutadiene in the ABS resin can be suppressed and a heat-resistant resin composition having excellent impact resistance can be obtained. That is, the present invention provides: (1) A method for producing a heat-resistant resin composition, comprising a step of melt-kneading a maleimide copolymer (A) and an ABS resin (B) in an extruder, in which the melt-kneading is carried out in the presence of at least one radical scavenger (C) selected from 2-t-butyl-6-(3'-t-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate and 2,4-di-t-amyl-6-[1-(3,5-di-t-amyl-2-hydroxyphenyl)ethyl]phenyl acrylate; (2) The method for producing a heat-resistant resin composition according to (1), wherein the melt-kneading is carried out at a cylinder temperature of a kneading section of an extruder exceeding 260° C.; (3) The method for producing a heat-resistant resin composition according to (1) or (2), wherein the maleimide copolymer (A) has a glass transition temperature of 175° C. to 210° C.; (4) The method for producing a heat-resistant resin composition according to any one of (1) to (3), wherein the content of the radical scavenger (C) is 0.1 to 0.6 parts by mass per 100 parts by mass of the total of the maleimide-based copolymer (A) and the ABS-based resin (B). (5) The method for producing a heat-resistant resin composition according to any one of (1) to (4), wherein the extruder is a twin-screw extruder. (6) The method for producing a heat-resistant resin composition according to any one of (1) to (5), wherein the heat-resistant resin composition has a Vicat softening temperature of 115° C. or higher. (7) The method for producing a heat-resistant resin composition according to any one of (1) to (6), wherein the melt-kneading is carried out in the presence of two or more antioxidants (D) selected from a hindered phenol-based antioxidant and a phosphorus-based antioxidant. Regarding. Effect of the Invention
[0006] In the method for producing a heat-resistant resin composition of the present invention, the maleimide copolymer (A) and the ABS resin (B) are melt-kneaded in an extruder in the presence of a radical scavenger, thereby suppressing deterioration of polybutadiene in the ABS resin and producing a heat-resistant resin composition having excellent impact resistance. [Brief description of the drawings]
[0007] [Figure 1] FIG. 2 is a schematic diagram showing a cylinder of a twin-screw extruder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] <Terminology explanation> In the present specification, for example, the description "A to B" means A or more and B or less.
[0009] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The following embodiments of the present invention are described in detail below. The embodiments can be combined with each other.
[0010] <1.Resin composition> The heat-resistant resin composition of the present invention is a heat-resistant resin composition obtained by melt-kneading a maleimide copolymer (A) and an ABS resin (B) in an extruder, and may contain an SAN resin when melt-kneading in the extruder. The Vicat softening temperature of the heat-resistant resin composition is preferably 115°C or higher, more preferably 120°C or higher. The production method of the present invention is more effective when the content of the maleimide copolymer having a high melt viscosity is high, that is, when the Vicat softening temperature of the heat-resistant resin composition is high, because a higher processing temperature is required.
[0011] <2. Maleimide-based copolymer (A)> The maleimide copolymer (A) is a copolymer having maleimide monomer units and styrene monomer units, and may further have acrylonitrile monomer units and unsaturated dicarboxylic anhydride monomer units in the present invention.
[0012] The maleimide monomer unit is, for example, N-alkylmaleimide such as N-methylmaleimide, N-butylmaleimide, and N-cyclohexylmaleimide, and N-phenylmaleimide, N-chlorophenylmaleimide, N-methylphenylmaleimide, N-methoxyphenylmaleimide, and N-tribromophenylmaleimide. Among these, N-phenylmaleimide is preferred. The maleimide monomer unit may be used alone or in combination of two or more kinds. For the maleimide monomer unit, for example, a raw material consisting of a maleimide monomer can be used. Alternatively, it can be obtained by imidizing a raw material consisting of an unsaturated dicarboxylic acid monomer unit with ammonia or a primary amine. The maleimide copolymer (A) preferably contains 30 to 70% by mass of maleimide monomer units, more preferably 35 to 60% by mass, in 100% by mass of the maleimide copolymer (A). The content of the maleimide monomer units is specifically, for example, 30, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 50, 55, 60, or 70% by mass, and may be within a range between any two of the numerical values exemplified here. If the content of the maleimide monomer units is within this range, the compatibility with the ABS resin (B) described later, which is an essential component of ABS resin and optionally contains at least one resin selected from ASA resin, AES resin, and SAN resin, is improved, and the impact strength of the resin composition is excellent. The content of the maleimide monomer units is a value measured by 13C-NMR.
[0013] The styrene monomer unit is styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, ethylstyrene, p-tert-butylstyrene, α-methylstyrene, α-methyl-p-methylstyrene, etc. Among these, styrene is preferred from the viewpoints of industrial availability, low cost use, copolymerization with various monomers, and light weight and excellent moldability. The styrene monomer unit may be used alone or in combination of two or more kinds. The maleimide copolymer (A) preferably contains 20 to 60 mass% of styrene monomer units, more preferably 35 to 55 mass% in 100 mass% of the maleimide copolymer (A). Specifically, for example, it is 20, 30, 40, 45, 46, 47, 48, 49, 50, 55, or 60 mass%, and may be within a range between any two of the numerical values exemplified here. If the content of the styrene monomer units is within this range, the compatibility with the ABS resin (B) described later, which is an essential component of ABS resin and optionally contains at least one resin selected from ASA resin, AES resin, and SAN resin, is improved, and the impact strength of the resin composition is excellent. The content of the styrene monomer units is a value measured by 13C-NMR.
[0014] The acrylonitrile-based monomer unit is acrylonitrile, methacrylonitrile, ethacrylonitrile, fumaronitrile, etc. Among these, acrylonitrile is preferred from the viewpoint of industrial availability. The acrylonitrile-based monomer unit may be used alone or in combination of two or more kinds. The maleimide copolymer (A) preferably contains 0 to 20 mass% of acrylonitrile monomer units, more preferably 0 to 15 mass%, in 100 mass% of the maleimide copolymer (A). Specifically, for example, it is 0, 5, 6, 7, 8, 9, 10, 15, or 20 mass%, and may be within a range between any two of the numerical values exemplified here. If the content of the acrylonitrile monomer units is within this range, the chemical resistance of the resin composition is excellent. The content of the acrylonitrile monomer units is a value measured by 13C-NMR.
[0015] The unsaturated dicarboxylic anhydride monomer unit is maleic anhydride, itaconic anhydride, citraconic anhydride, aconitic anhydride, etc. Among these, maleic anhydride is preferred from the viewpoint of industrial availability. The unsaturated dicarboxylic anhydride monomer unit may be used alone or in combination of two or more kinds. The maleimide copolymer (A) preferably contains 0 to 10 mass% of unsaturated dicarboxylic anhydride monomer units, more preferably 0 to 5 mass% in 100 mass% of the maleimide copolymer (A). Specifically, for example, it is 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 mass%, and may be within a range between any two of the numerical values exemplified here. If the content of the unsaturated dicarboxylic anhydride monomer units is within this range, the thermal stability of the maleimide copolymer is excellent. The content of the unsaturated dicarboxylic anhydride monomer units is a value measured by a titration method.
[0016] In one embodiment of the present invention, the maleimide copolymer (A) preferably contains 30 to 70% by mass of maleimide monomer units, 20 to 60% by mass of styrene monomer units, 0 to 20% by mass of acrylonitrile monomer units, and 0 to 10% by mass of unsaturated dicarboxylic anhydride monomer units in 100% by mass of the maleimide copolymer (A). More preferably, the maleimide copolymer (A) contains 35 to 60% by mass of maleimide monomer units, 35 to 55% by mass of styrene monomer units, 0 to 15% by mass of acrylonitrile monomer units, and 0 to 5% by mass of unsaturated dicarboxylic anhydride monomer units in 100% by mass of the maleimide copolymer (A). When the constituent units are within the above ranges, the maleimide copolymer (A) has excellent fluidity, heat resistance, and thermal stability.
[0017] In terms of efficiently improving the heat resistance of the resin composition, the maleimide copolymer (A) preferably has a glass transition temperature (midpoint glass transition temperature: Tmg) of 175° C. to 210° C., more preferably 185° C. to 205° C. The glass transition temperature is a value measured by DSC under the measurement conditions described below. Device name: Seiko Instruments Inc. Robot DSC6200 Heating rate: 10℃ / min
[0018] The weight average molecular weight (Mw) of the maleimide copolymer (A) is preferably 60,000 to 150,000, more preferably 70,000 to 140,000. Specifically, for example, it may be 6, 7, 8, 9, 10, 11, 12, 13, 14, or 150,000, and may be within a range between any two of the numerical values exemplified here. If the weight average molecular weight (Mw) of the maleimide copolymer (A) is within the above range, the impact strength of the resin composition is excellent. In order to control the weight average molecular weight (Mw) of the maleimide copolymer (A), in addition to adjusting the polymerization temperature, polymerization time, and amount of polymerization initiator added, there are methods such as adjusting the solvent concentration and amount of chain transfer agent added. The weight average molecular weight of the maleimide copolymer (A) is a value measured in terms of polystyrene by gel permeation chromatography (GPC) and was measured under the following conditions. Device name: SYSTEM-21 Shodex (Showa Denko Co., Ltd.) Column: 3 PL gel MIXED-B in series Temperature: 40℃ Detection: Differential refractive index Solvent: Tetrahydrofuran Concentration: 2% by mass Calibration curve: Prepared using standard polystyrene (PS) (PL Corporation).
[0019] A known method can be used to produce the maleimide copolymer (A). For example, there is a method of copolymerizing a monomer mixture consisting of a styrene monomer, a maleimide monomer, an unsaturated dicarboxylic anhydride monomer, and other copolymerizable monomers. There is also a method of copolymerizing a monomer mixture consisting of a styrene monomer, an unsaturated dicarboxylic anhydride monomer, and other copolymerizable monomers, and then reacting ammonia or a primary amine to imidize a part of the unsaturated dicarboxylic anhydride monomer units and convert them into maleimide monomer units (hereinafter referred to as a "post-imidization method").
[0020] The polymerization mode of the maleimide copolymer (A) may be, for example, solution polymerization or bulk polymerization. From the viewpoint that the copolymerization while performing the portionwise addition or the like can obtain the maleimide copolymer (A) having a more uniform copolymerization composition, solution polymerization is preferred. The solvent for the solution polymerization is preferably non-polymerizable from the viewpoint that by-products are unlikely to be produced and adverse effects are small. For example, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, acetophenone, etc., ethers such as tetrahydrofuran and 1,4-dioxane, aromatic hydrocarbons such as benzene, toluene, xylene, chlorobenzene, etc., N,N-dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, etc., and methyl ethyl ketone and methyl isobutyl ketone are preferred from the viewpoint of ease of solvent removal during volatilization and recovery of the maleimide copolymer (A). The polymerization process may be any of a continuous polymerization method, a batch method (batch method), and a semi-batch method. The polymerization method is not particularly limited, but radical polymerization is preferred from the viewpoint that it is possible to produce the copolymer with good productivity by a simple process.
[0021] In the solution polymerization or bulk polymerization, a polymerization initiator and a chain transfer agent can be used, and the polymerization temperature is preferably in the range of 80 to 150°C. The polymerization initiator is, for example, an azo compound such as azobisisobutyronitrile, azobiscyclohexanecarbonitrile, azobismethylproponitrile, or azobismethylbutyronitrile, or a peroxide such as benzoyl peroxide, t-butylperoxybenzoate, 1,1-di(t-butylperoxy)cyclohexane, t-butylperoxyisopropylmonocarbonate, t-butylperoxy-2-ethylhexanoate, di-t-butylperoxide, dicumylperoxide, or ethyl-3,3-di-(t-butylperoxy)butyrate, and one or more of these may be used in combination. From the viewpoint of the polymerization reaction rate and polymerization rate control, it is preferable to use an azo compound or an organic peroxide with a 10-hour half-life of 70 to 120°C. The amount of the polymerization initiator used is not particularly limited, but is preferably 0.1 to 1.5% by mass, more preferably 0.1 to 1.0% by mass, based on 100% by mass of the total monomer units. If the amount of the polymerization initiator used is 0.1% by mass or more, a sufficient polymerization rate can be obtained, which is preferable. If the amount of the polymerization initiator used is 1.5% by mass or less, the polymerization rate can be suppressed, making it easy to control the reaction and to easily obtain the target molecular weight. Examples of the chain transfer agent include n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, α-methylstyrene dimer, ethyl thioglycolate, limonene, and terpinolene. The amount of the chain transfer agent used is not particularly limited as long as it is within a range in which the target molecular weight can be obtained, but is preferably 0.1 to 0.8% by mass, more preferably 0.15 to 0.5% by mass, based on 100% by mass of the total monomer units. If the amount of the chain transfer agent used is 0.1% by mass to 0.8% by mass, the target molecular weight can be easily obtained.
[0022] The introduction of maleimide monomer units into the maleimide copolymer (A) can be achieved by copolymerizing maleimide monomers or by post-imidization. The post-imidization method is preferred because it reduces the amount of maleimide monomers remaining in the maleimide copolymer (A). The post-imidization method is a method in which a monomer mixture consisting of a styrene monomer, an unsaturated dicarboxylic anhydride monomer, and other copolymerizable monomers is copolymerized, and then a part of the unsaturated dicarboxylic anhydride monomer units is imidized by reacting with ammonia or a primary amine to convert them into maleimide monomer units. Examples of primary amines include alkylamines such as methylamine, ethylamine, n-propylamine, iso-propylamine, n-butylamine, n-pentylamine, n-hexylamine, n-octylamine, cyclohexylamine, and decylamine, as well as chlorine- or bromine-substituted alkylamines, aniline, toluidine, and naphthylamine, among which aniline is preferred. These primary amines may be used alone or in combination of two or more. In the post-imidization, a catalyst may be used to improve the dehydration ring-closing reaction in the reaction between the primary amine and the unsaturated dicarboxylic anhydride monomer unit. The catalyst is, for example, a tertiary amine such as trimethylamine, triethylamine, tripropylamine, tributylamine, N,N-dimethylaniline, or N,N-diethylaniline. The post-imidization temperature is preferably 100 to 250°C, more preferably 120 to 200°C. If the temperature of the imidization reaction is 100°C or higher, the reaction rate is improved, which is preferable from the viewpoint of productivity. If the temperature of the imidization reaction is 250°C or lower, it is preferable because the decrease in physical properties due to thermal deterioration of the maleimide copolymer (A) can be suppressed.
[0023] A known method can be used to remove volatile matters such as the solvent used in the solution polymerization and unreacted monomers from the solution after the completion of the solution polymerization of the maleimide copolymer (A) or the solution after the completion of the post-imidization (devolatilization method). For example, a vacuum devolatilization tank equipped with a heater or a devolatilization extruder equipped with a vent can be used. The devolatilized molten maleimide copolymer (A) is transferred to a granulation process, extruded into strands through a multi-hole die, and processed into pellets by a cold cut method, an air hot cut method, or an underwater hot cut method.
[0024] The content of the maleimide copolymer (A) in the resin composition is preferably 5 to 45% by mass, more preferably 7 to 35% by mass, even more preferably 10 to 30% by mass, and even more preferably 20 to 30% by mass, when the total amount of the maleimide copolymer (A) and the ABS resin (B) is taken as 100% by mass. Specifically, for example, it is 5, 10, 15, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 35, 40, or 45% by mass, and may be within a range between any two of the numerical values exemplified here. If the content of the maleimide copolymer (A) is too small, the heat resistance of the resin composition may not be sufficiently improved. If it is too large, the flowability may decrease and the moldability may deteriorate. The resin contained in the resin composition may be substantially only the maleimide copolymer (A) and the ABS resin.
[0025] <3.ABS resin (B)> The ABS resin (B) is a resin that contains ABS resin as an essential component, and optionally contains at least one resin selected from ASA resin, AES resin, and SAN resin. The ABS resin is a graft copolymer obtained by graft copolymerizing at least a styrene monomer and an acrylonitrile monomer to a rubber-like polymer. For example, butadiene-based rubber such as polybutadiene and styrene-butadiene copolymer is used as the rubber-like polymer. Two or more of these rubber-like polymers may be used in combination during graft copolymerization. When an acrylic rubber made of butyl acrylate or ethyl acrylate is used, an ASA resin may be used in combination, and when an ethylene-based rubber such as an ethylene-α-olefin copolymer is used, an AES resin may be used in combination. The content of the ABS resin in the ABS resin (B) is preferably 10 to 100 mass% in 100 mass% of the ABS resin (B), and more preferably 15 to 60 mass%. Specifically, for example, it is 10, 15, 20, 25, 30, 35, 40, 45, 50, 60, 70, or 100 mass%, and may be within a range between any two of the numerical values exemplified here. The ABS resin (B) may be substantially only the ABS resin. From the viewpoint of impact strength, the content of the polybutadiene component in the ABS resin (B) is preferably 10 to 35 mass% and more preferably 15 to 30 mass% in 100 mass% of the ABS resin (B).Specifically, the content is, for example, 10, 15, 20, 25, 30, or 35 mass%, and may be within a range between any two of the numerical values exemplified here.
[0026] A known method can be used to produce a graft copolymer such as an ABS resin. For example, a production method using emulsion polymerization or continuous bulk polymerization can be used. The method using emulsion polymerization is preferred because it is easy to adjust the content of the rubber-like polymer in the final resin composition.
[0027] The method for producing a graft copolymer by emulsion polymerization includes a method in which a styrene-based monomer and an acrylonitrile-based monomer are emulsion-graft-polymerized to a latex of a rubber-like polymer (hereinafter referred to as "emulsion graft polymerization method"). A latex of a graft copolymer can be obtained by the emulsion graft polymerization method.
[0028] In the emulsion graft polymerization method, water, an emulsifier, a polymerization initiator, and a chain transfer agent are used, and the polymerization temperature is preferably in the range of 30 to 90°C. Examples of the emulsifier include an anionic surfactant, an onion surfactant, and an amphoteric surfactant. Examples of the polymerization initiator include organic peroxides such as cumene hydroperoxide, diisopropyl ene peroxide, t-butyl peroxyacetate, t-hexyl peroxybenzoate, and t-butyl peroxybenzoate, persulfates such as potassium persulfate and ammonium persulfate, azo compounds such as azobisbutyronitrile, reducing agents such as iron ions, secondary reducing agents such as sodium formaldehyde sulfoxylate, and chelating agents such as disodium ethylenediamine tetraacetate. Examples of the chain transfer agent include n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, α-methylstyrene dimer, ethyl thioglycolate, limonene, and terpinolene.
[0029] The latex of the graft copolymer can be coagulated by a known method, and the graft copolymer can be recovered. For example, a coagulant is added to the latex of the graft copolymer to coagulate it, and the coagulated latex is washed and dehydrated in a dehydrator, and then a drying process is performed to obtain a powdery graft copolymer.
[0030] The content of the rubber-like polymer in the graft copolymer obtained by emulsion graft polymerization is preferably 40 to 70% by mass, more preferably 45 to 65% by mass, from the viewpoint of impact resistance. The content of the rubber-like polymer can be adjusted, for example, by changing the ratio of the styrene-based monomer and the acrylonitrile-based monomer to the rubber-like polymer during emulsion graft polymerization.
[0031] From the viewpoints of impact resistance and chemical resistance, the constituent units excluding the rubber-like polymer of the graft copolymer obtained by emulsion graft polymerization preferably contain 65 to 85 mass % of styrene-based monomer units and 15 to 35 mass % of acrylonitrile-based monomer units.
[0032] The gel fraction of the graft copolymer is preferably particulate. The gel fraction is a rubber-like polymer particle obtained by graft copolymerization of a styrene-based monomer and an acrylonitrile-based monomer, and is a component that is insoluble in organic solvents such as methyl ethyl ketone and toluene and is separated by centrifugation. An occlusion structure in which a styrene-acrylonitrile-based copolymer is encapsulated in particulate form may be formed inside a rubber-like polymer particle. When a graft copolymer and a styrene-acrylonitrile-based copolymer are melt-blended, the gel fraction exists as a particulate dispersed phase in the continuous phase of the styrene-acrylonitrile-based copolymer. The gel fraction is calculated by dissolving a mass W of the graft copolymer in methyl ethylene ketone, centrifuging the mixture at 20,000 rpm using a centrifuge to settle the insoluble fraction, removing the supernatant by decantation to obtain the insoluble fraction, and calculating the mass S of the dried insoluble fraction after vacuum drying using the formula: gel fraction (mass%) = (S / W) x 100. Similarly, a resin composition obtained by melt-blending a graft copolymer and a styrene-acrylonitrile copolymer can be dissolved in methyl ethyl ketone and centrifuged to calculate the gel content.
[0033] The volume average particle size of the gel portion of the graft copolymer is preferably in the range of 0.10 to 1.0 μm, more preferably 0.15 to 0.50 μm, from the viewpoint of impact resistance and the appearance of the molded product. The volume average particle size is a value calculated from an image analysis of particles dispersed in a continuous phase by cutting ultra-thin slices from pellets of a resin composition obtained by melt-blending a graft copolymer and a styrene-acrylonitrile copolymer, observing the slices with a transmission electron microscope (TEM). The volume average particle size can be adjusted, for example, by the particle size of the latex of the rubber-like polymer used in emulsion graft polymerization. The particle size of the latex of the rubber-like polymer can be adjusted by the method of adding an emulsifier or the amount of water used during emulsion polymerization, but in order to achieve a preferred range, the polymerization time is long and the productivity is low, so there is a method in which a rubber-like polymer with a particle size of about 0.1 μm is polymerized in a short time, and the rubber particles are enlarged using a chemical coagulation method or a physical coagulation method.
[0034] From the viewpoint of impact resistance, the graft ratio of the graft copolymer is preferably 10 to 100% by mass, more preferably 20 to 70% by mass. The graft ratio is a value calculated from the gel content (G) and the content of the rubber-like polymer (RC) by the formula: graft ratio (mass%) = [(G-RC) / R] x 100. The graft ratio represents the amount of styrene-acrylonitrile copolymer bound to the rubber-like polymer particles by grafts contained per unit mass of the rubber-like polymer and the amount of styrene-acrylonitrile copolymer contained in the particles. The graft ratio can be adjusted, for example, by the ratio of monomer to rubber-like polymer, the type and amount of initiator, the amount of chain transfer agent, the amount of emulsifier, the polymerization temperature, the method of charging (lump / multi-stage / continuous), the rate of addition of monomer, etc., during emulsion graft polymerization.
[0035] The degree of swelling in toluene of the graft copolymer is preferably 5 to 20 times from the viewpoint of impact resistance and the appearance of the molded product. The degree of swelling in toluene represents the degree of crosslinking of the rubber-like polymer particles, and is calculated from the mass ratio of the graft copolymer in a state where it is swollen with toluene, the insoluble matter being separated by centrifugation or filtration, and the mass of the dried state where the toluene is removed by vacuum drying. The degree of swelling in toluene is affected by the degree of crosslinking of the rubber-like polymer used in emulsion graft polymerization, for example, and can be adjusted by the initiator, emulsifier, polymerization temperature, and addition of a multifunctional monomer such as divinylbenzene during emulsion polymerization of the rubber-like polymer.
[0036] SAN resin is a copolymer having styrene-based monomer units and acrylonitrile-based monomer units, and an example is a styrene-acrylonitrile-based copolymer.
[0037] Other copolymerizable monomers for SAN resin include (meth)acrylic acid ester monomers such as methyl methacrylate, acrylic acid ester monomers such as butyl acrylate and ethyl acrylate, (meth)acrylic acid monomers such as methacrylic acid, acrylic acid monomers such as acrylic acid, and N-substituted maleimide monomers such as N-phenylmaleimide.
[0038] The constituent units of the SAN resin are preferably 60 to 90% by mass of styrene monomer units and 10 to 40% by mass of vinyl cyanide monomer units, and more preferably 65 to 80% by mass of styrene monomer units and 20 to 35% by mass of vinyl cyanide monomer units. If the constituent units are within the above ranges, the balance between impact strength and fluidity of the resulting resin composition is excellent. The values of the styrene monomer units and vinyl cyanide monomer units are values measured by 13C-NMR.
[0039] A known method can be used to produce SAN resin. For example, it can be produced by bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. As the operation method of the reaction apparatus, any of a continuous type, a batch type (batch type), and a semi-batch type can be applied. From the viewpoints of quality and productivity, bulk polymerization or solution polymerization is preferred, and continuous type is preferred. Examples of the solvent for bulk polymerization or solution polymerization include alkylbenzenes such as benzene, toluene, ethylbenzene, and xylene, ketones such as acetone and methyl ethyl ketone, and aliphatic hydrocarbons such as hexane and cyclohexane.
[0040] In bulk polymerization or solution polymerization of SAN resin, a polymerization initiator and a chain transfer agent can be used, and the polymerization temperature is preferably in the range of 120 to 170° C. Examples of the polymerization initiator include peroxyketals such as 1,1-di(t-butylperoxy)cyclohexane, 2,2-di(t-butylperoxy)butane, 2,2-di(4,4-di-t-butylperoxycyclohexyl)propane, and 1,1-di(t-amylperoxy)cyclohexane; hydroperoxides such as cumene hydroperoxide and t-butyl hydroperoxide; alkyl peroxides such as t-butyl peroxyacetate and t-amyl peroxyisononanoate; dialkyl peroxides such as t-butylcumyl peroxide, di-t-butyl peroxide, dicumyl peroxide, and di-t-hexyl peroxide; peroxyesters such as t-butylperoxyacetate, t-butylperoxybenzoate, and t-butylperoxyisopropyl monocarbonate; peroxycarbonates such as t-butylperoxyisopropyl carbonate and polyethertetrakis(t-butylperoxycarbonate); N,N'-azobis(cyclohexane-1-carbonitrile), N,N'-azobis(2-methylbutyronitrile), N,N'-azobis(2,4-dimethylvaleronitrile), and N,N'-azobis[2-(hydroxymethyl)propionitrile]; and these may be used alone or in combination of two or more. Examples of chain transfer agents include n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, α-methylstyrene dimer, ethyl thioglycolate, limonene, and terpinolene.
[0041] A known method can be used to remove volatile matters such as unreacted monomers and the solvent used in the solution polymerization from the solution after the polymerization of SAN resin is completed. For example, a vacuum devolatilization tank equipped with a preheater or a devolatilization extruder equipped with a vent can be used. The devolatilized SAN resin in a molten state is transferred to a granulation process, extruded into strands through a multi-hole die, and processed into pellets by a cold cut method, an air hot cut method, or an underwater hot cut method.
[0042] The weight average molecular weight of the SAN resin is preferably 50,000 to 250,000, more preferably 70,000 to 200,000, from the viewpoint of impact resistance and moldability of the resin composition. Specifically, for example, it is 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 200,000, and may be within a range between any two of the numerical values exemplified here. The weight average molecular weight of the SAN resin is a value measured in THF solvent using gel permeation chromatography (GPC) in terms of polystyrene, and is a value measured in the same manner as the maleimide copolymer (A). The weight average molecular weight can be adjusted by the type and amount of chain transfer agent, solvent concentration, polymerization temperature, and type and amount of polymerization initiator during polymerization.
[0043] For example, two types of ABS resin (B) may be used: a powdered ABS resin obtained by emulsion polymerization and a pelleted SAN resin obtained by continuous bulk polymerization. Another method is to melt-blend the powdered ABS resin obtained by emulsion polymerization and the pelleted SAN resin obtained by continuous bulk polymerization in an extruder or the like to obtain pelleted ABS resin (B).
[0044] A known method can be used for melt-kneading the maleimide copolymer (A) and the ABS resin (B) using an extruder. Known devices can be used as the extruder, and examples of such devices include twin-screw extruders, single-screw extruders, multi-screw extruders, and continuous kneaders with twin-screw rotors. From the viewpoint of being able to arbitrarily set the screw configuration and adjust the kneading properties, it is preferable to use a twin-screw extruder, and a co-rotating intermeshing twin-screw extruder is generally widely used and is more preferable.
[0045] In the twin-screw extruder according to the embodiment of the present invention, as shown in FIG. 1, the space in which the cylinder is disposed is divided into a plurality of sections from the inlet section to the outlet section of the raw material, and the temperature of each section can be controlled. The cylinder temperature of the kneading section in the present invention is the set temperature of the section in which the kneading section cylinder (mixing element) is disposed and which has the highest temperature among the sections in which the materials to be melt-kneaded are kneaded. The cylinder temperature of the kneading section of the extruder according to the embodiment of the present invention is a temperature exceeding 260° C., and preferably 270 to 330° C. If the cylinder temperature of the kneading section is 260° C. or lower, the dispersibility of the maleimide copolymer deteriorates, or the melt viscosity is too high, making extrusion difficult.
[0046] <4. Radical Scavenger (C)> The melt-kneading is carried out in the presence of at least one radical scavenger (C) selected from 2-t-butyl-6-(3'-t-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate and 2,4-di-t-amyl-6-[1-(3,5-di-t-amyl-2-hydroxyphenyl)ethyl]phenyl acrylate. In the absence of the radical scavenger, the impact resistance of the heat-resistant resin composition decreases. The radical scavenger (C) can be fed to the extruder together with the maleimide copolymer (A) and the ABS resin (B) during melt-kneading in the extruder. It may also be incorporated in the maleimide copolymer (A) or the ABS resin (B) beforehand. The content of the radical scavenger (C) relative to 100 parts by mass of the total of the maleimide copolymer (A) and the ABS resin (B) is preferably 0.1 to 0.6 parts by mass, more preferably 0.2 to 0.4 parts by mass, specifically, for example, 0.1, 0.2, 0.3, 0.4, 0.5 or 0.6, and may be within a range between any two of the numerical values exemplified here. The content (mass ratio) of the polybutadiene component in the ABS resin relative to the radical scavenger (C) (polybutadiene content / radical scavenger (C)) is preferably 30 to 200, and more preferably 50 to 110. Specifically, for example, it is 30, 35, 40, 45, 50, 55, 70, 80, 90, 100, 110, 120, 150, or 200, and may be within a range between any two of the numerical values exemplified here.
[0047] In the melt-kneading, an antioxidant can be used in combination, and the antioxidant is preferably a hindered phenol-based antioxidant, and may be used in combination with a phosphorus-based antioxidant. The addition of the antioxidant can prevent yellowing during molding or practical use of the heat-resistant resin composition.
[0048] A hindered phenol-based antioxidant is an antioxidant that has a phenolic hydroxyl group in its basic structure. Examples of the hindered phenol antioxidant include octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, ethylene bis(oxyethylene) bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], 3,9-bis[2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 4,6-bis(octylthiomethyl)-o-cresol, 4,6-bis[(dodecylthio)methyl]-o-cresol, 2,4-dimethyl-6-(1-methyl pentadecyl)phenol, tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane, 4,4'-thiobis(6-t-butyl-3-methylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 4,4'-butylidenebis(3-methyl-6-t-butylphenol), bis-[3,3-bis-(4'-hydroxy-3'-tert-butylphenyl)-butanoic acid]-glycol ester, 2-t-butyl-6-(3-t-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate, 2-[1-(2-hydroxy-3,5-di-t-pentylphenyl)ethyl]-4,6-di-t-pentylphenyl acrylate, and the like. Preferred are octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, ethylene bis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], and pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. More preferred is octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate. The hindered phenol-based antioxidants may be used alone or in combination of two or more.
[0049] Phosphorus-based antioxidants are phosphorous esters, which are trivalent phosphorus compounds. Examples of phosphorus-based antioxidants include 6-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-t-butylbenz[d,f][1,3,2]dioxaphosphepine, 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, 2,2'-methylenebis(4,6-di-tert-butyl-1-phenyloxy)(2-ethylhexyloxy)phosphorus, and tris(2,4-di-tert-butylphenyl)phosphite. , bis[2,4-bis(1,1-dimethylethyl)-6-methylphenyl]ethyl ester phosphorous acid, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, cyclic neopentanetetraylbis(octadecyl phosphite), bis(nonylphenyl)pentaerythritol diphosphite, 4,4'-biphenylene diphosphinic acid tetrakis(2,4-di-tert-butylphenyl), 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tetrakis(2,4-di-tert-butyl-5-methylphenyl)-4,4'-biphenylene diphosphonite, and the like. Preferred are 6-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-t-butylbenz[d,f][1,3,2]dioxaphosphepine, 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, 2,2'-methylenebis(4,6-di-tert-butyl-1-phenyloxy)(2-ethylhexyloxy)phosphorus, tris(2,4-di-tert-butylphenyl)phosphite, and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite.More preferred are 6-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-t-butylbenz[d,f][1,3,2]dioxaphosphepine, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl)phosphite, and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, and even more preferred are 6-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-t-butylbenz[d,f][1,3,2]dioxaphosphepine, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite. The phosphorus-based antioxidants may be used alone or in combination of two or more kinds.
[0050] When producing the heat-resistant resin composition, other resin components, impact resistance modifiers, flowability modifiers, hardness modifiers, antioxidants, inorganic fillers, matting agents, flame retardants, flame retardant assistants, drip prevention agents, sliding properties imparting agents, heat dissipation materials, electromagnetic wave absorbing materials, plasticizers, lubricants, release agents, ultraviolet absorbing agents, light stabilizers, antibacterial agents, antifungal agents, antistatic agents, carbon black, titanium oxide, pigments, dyes, and the like may be blended within the scope not impairing the effects of the present invention. EXAMPLES
[0051] The following detailed description will be given using examples, but the present invention is not limited to the following examples.
[0052] <Production Example of Maleimide Copolymer (A-1)> A maleimide copolymer (A-1) was produced by the following method. Into an autoclave with a volume of about 120 liters equipped with a stirrer, 62 parts by mass of styrene, 11 parts by mass of maleic anhydride, 0.2 parts by mass of 2,4-diphenyl-4-methyl-1-pentene, and 31 parts by mass of methyl ethyl ketone were charged. After replacing the inside of the system with nitrogen gas, the temperature was raised to 92 °C, and a solution prepared by dissolving 28 parts by mass of maleic anhydride and 0.19 parts by mass of t-butyl peroxy-2-ethylhexanoate in 110 parts by mass of methyl ethyl ketone was continuously added over 7 hours. After the addition, the temperature was raised to 120 °C and reacted for 30 minutes to complete the polymerization. Then, 35 parts by mass of aniline and 0.6 parts by mass of triethylamine were added to the polymerization solution and reacted at 140 °C for 7 hours. The imidized reaction solution after the completion of the reaction was charged into a vent type screw extruder to remove volatile components, and a pelletized maleimide copolymer (A-1) was obtained. (A-1) consisted of 48% by mass of styrene units, 51% by mass of N-phenylmaleimide units, and 1% by mass of maleic anhydride units. The weight average molecular weight Mw was 130,000, and the glass transition temperature (midpoint glass transition temperature: Tmg) was 202 °C.
[0053] <ABS resin (B-1)> The ABS resin (B-1) was prepared by the emulsion graft polymerization method. 97 parts by mass of polybutadiene latex (solid content concentration: 50% by mass, average particle diameter: 0.3 μm), 12 parts by mass of styrene-butadiene latex with a styrene content of 24% by mass (solid content concentration: 70% by mass, average particle diameter: 0.5 μm), 1 part by mass of sodium stearate, 0.2 part by mass of sodium formaldehyde sulfoxylate, 0.01 part by mass of tetrasodium ethylenediaminetetraacetate, 0.005 part by mass of ferrous sulfate, and 200 parts of pure water were charged into a reaction vessel equipped with a stirrer, and the temperature was heated to 50°C. 43 parts by mass of a monomer mixture of 75% by mass of styrene and 25% by mass of acrylonitrile, 0.2 part by mass of t-dodecyl mercaptan, and 0.06 part by mass of t-butyl peroxyacetate were continuously added in portions over 5 hours. After the completion of the addition in portions, 0.04 part by mass of diisopropylbenzene peroxide was added, and the polymerization was further completed at 70°C over 2 hours to obtain a latex of the ABS resin. After adding 0.3 part of Irganox 1076 (manufactured by Ciba Specialty Chemicals) to the obtained latex, coagulation was carried out using magnesium sulfate and sulfuric acid so that the pH of the slurry during coagulation was 6.8. After washing, dehydration, and drying, a powdery ABS resin (B-1) was obtained. From the blending ratio of the raw materials, the rubbery polymer content was 57% by mass. The structural units excluding the rubbery polymer were measured by NMR, and the styrene unit was 75% by mass and the acrylonitrile unit was 25% by mass. From the observation of the transmission electron microscope after forming the resin composition, the ABS resin was dispersed in a particulate form, and the volume average particle diameter was 0.4 μm.
[0054] <SAN resin (B-2)> The SAN resin (B-2) was produced by the following method. It was prepared by continuous bulk polymerization. One completely mixed tank-type stirred tank with a capacity of 30 L was used as the reactor, and polymerization was carried out. A raw material solution containing 60% by mass of styrene, 22% by mass of acrylonitrile, and 18% by mass of ethylbenzene was prepared and continuously supplied to the reactor at a flow rate of 9.5 L / h. Also, t-butyl peroxyisopropyl monocarbonate was continuously added to the supply line of the raw material solution at a concentration of 160 ppm as a polymerization initiator, and n-dodecyl mercaptan was continuously added at a concentration of 400 ppm as a chain transfer agent. The reaction temperature of the reactor was adjusted to 145°C. The polymer solution continuously withdrawn from the reactor was supplied to a vacuum devolatilization tank equipped with a preheater, and unreacted styrene, acrylonitrile, and ethylbenzene were separated. The temperature of the preheater was adjusted so that the polymer temperature in the devolatilization tank was 235°C, and the pressure in the devolatilization tank was 0.4 kPa. The polymer was extracted from the vacuum devolatilization tank by a gear pump, extruded in a strand shape, cooled with cooling water, and cut to obtain pelletized SAN resin (B-2). The constituent units of (B-2) were 73.5% by mass of styrene units and 26.5% by mass of acrylonitrile units. Also, the weight average molecular weight was 146,000.
[0055] <ABS resin (B-3)> Commercially available general-purpose ABS resin GR-3000 (manufactured by Denka Co., Ltd.) was used.
[0056] <Examples and Comparative Examples> A maleimide copolymer, an ABS resin, a radical scavenger, and an antioxidant were melt-kneaded using an extruder under the compounding and conditions shown in Table 1 to produce a heat-resistant resin composition. As the extruder, a twin-screw extruder (TEM-35B manufactured by Toshiba Machine Co., Ltd.) was used. Extrusion was carried out at the cylinder temperature of the kneading section shown in Table 1, with a screw rotation speed of 250 rpm and a feed rate of 30 kg / hr. The radical scavenger and antioxidant used were as follows. The evaluation results are shown in Table 1. In Comparative Example 3, the cylinder temperature of the kneading section was low, and extrusion at the specified discharge rate was impossible due to torque over. (C-1) 2-t-butyl-6-(3'-t-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate (Sumitomo Chemical Co., Ltd., Sumilizer GM ) (C-2) 2,4-di-t-amyl-6-[1-(3,5-di-t-amyl-2-hydroxyphenyl)ethyl]phenyl acrylate (Sumitomo Chemical Co., Ltd. Sumilizer GS ) (D-1) Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Irganox 1010, manufactured by BASF Japan Ltd.) (D-2) Tris(2,4-di-tert-butylphenyl)phosphite (Irgafos 168, manufactured by BASF Japan Ltd.)
[0057] (Melt Mass Flow Rate) The melt mass flow rate was measured at 220°C and a load of 98N based on JIS K7210.
[0058] (Vicat softening temperature) The Vicat softening point was measured using a test piece of 10 mm x 10 mm and 4 mm thick, according to the JIS K7206 50 method (load 50N, heating rate 50℃ / hour). The measuring machine used was a HDT&VSPT tester manufactured by Toyo Seiki Seisakusho Co., Ltd.
[0059] (Charpy impact strength) The Charpy impact strength was measured based on JIS K7111-1 using a notched test piece and edgewise impact direction. The measuring machine used was a digital impact tester manufactured by Toyo Seiki Seisakusho Co., Ltd.
[0060] (Hue YI value) A plate (9 cm x 5 cm) was molded at a molding temperature of 240°C using an injection molding machine IS-50EP (manufactured by Toshiba Machine Co., Ltd.), and the yellowness index YI was measured using a color difference meter COLOR-7e2 (manufactured by Kurabo Industries, Ltd.).
[0061] [Table 1]
[0062] From the results in Table 1, it can be seen that in order to melt-knead a heat-resistant resin composition, it is necessary to set the cylinder temperature of the kneading section relatively high, but by melt-kneading in the presence of a radical scavenger, it is possible to produce a heat-resistant resin composition with excellent impact resistance. [Industrial Applicability]
[0063] According to the manufacturing method of the present invention, a heat-resistant resin composition having excellent impact resistance can be obtained even when the maleimide copolymer and the ABS resin are melt-kneaded at a high processing temperature. Since melt-kneading at a high processing temperature is possible, a maleimide copolymer having high heat resistance can be used, and the heat resistance of the ABS resin can be improved by adding a small amount. In addition, it is possible to increase the blending amount of the maleimide copolymer having a high melt viscosity, and it is also possible to produce a heat-resistant resin composition having high heat resistance.
Claims
1. A method for producing a heat-resistant resin composition, comprising a step of melt-kneading a maleimide copolymer (A) and an ABS resin (B) containing an ABS resin in an extruder, the melt-kneading being carried out in the presence of at least one radical scavenger (C) selected from 2-t-butyl-6-(3'-t-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate and 2,4-di-t-amyl-6-[1-(3,5-di-t-amyl-2-hydroxyphenyl)ethyl]phenyl acrylate; the content (mass ratio) of the polybutadiene component in the ABS resin relative to the radical scavenger (C) is 30 to 200; The method for producing a heat-resistant resin composition, wherein the melt-kneading is carried out at a cylinder temperature in a kneading section of the extruder exceeding 260°C.
2. A method for producing a heat-resistant resin composition according to claim 1, wherein the content of the ABS resin in 100 mass% of the ABS resin (B) is 10 to 50 mass%.
3. The method for producing a heat-resistant resin composition according to claim 1 or 2, wherein the maleimide-based copolymer (A) has a glass transition temperature of 175°C to 210°C.
4. The method for producing a heat-resistant resin composition according to any one of claims 1 to 3, wherein the content of the radical scavenger (C) is 0.1 to 0.6 parts by mass per 100 parts by mass of the total of the maleimide-based copolymer (A) and the ABS-based resin (B).
5. The method for producing a heat-resistant resin composition according to any one of claims 1 to 4, wherein the extruder is a twin-screw extruder.
6. The method for producing a heat-resistant resin composition according to any one of claims 1 to 5, wherein the heat-resistant resin composition has a Vicat softening temperature of 115°C or higher.
7. The method for producing a heat-resistant resin composition according to any one of claims 1 to 6, wherein the melt-kneading is carried out in the presence of two or more antioxidants (D) selected from a hindered phenol-based antioxidant and a phosphorus-based antioxidant.
Citation Information
Patent Citations
Thermoplastic resin composition
JP1983183729A
Production of thermoplastic resin having excellent impact resistance
JP1993078430A
Maleimide heat resistance-imparting material
JP2003041080A
Maleimide-compound-containing rubber-reinforced styrene resin composition excellent in heat stability
JP2005097343A
Optical anisotropic film and production method of optical anisotropic film
JP2016091022A